2017
DOI: 10.1007/s10096-017-2964-1
|View full text |Cite|
|
Sign up to set email alerts
|

A new concept and a comprehensive evaluation of SYSMEX UF-1000i  flow cytometer to identify culture-negative urine specimens in patients with UTI

Abstract: Urinary tract infections (UTIs) are among the most common bacterial infections in men and urine culture is gold standard for diagnosis. Considering the high prevalence of culture-negative specimens, any method that identifies such specimens is of interest. The aim was to evaluate a new screening concept for flow cytometry analysis (FCA). The outcomes were evaluated against urine culture, uropathogen species and three conventional screening methods. A prospective, consecutive study examined 1,312 urine specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…However, high sensitivity could be shown with our parameter too, even with a cut-off of 10 4 cfu/mL [ 15 , 16 , 31 ]. Recently, a Swedish study presented a linear discriminant analysis using bacteria and leukocytes on a log scale [ 29 ] similar to Fig 2A . The parameters were slightly different from the parameters presented in this article, which might be due to another cut-off of urine culture bacterial growth (≥10 3 cfu/mL) and the use of Sysmex UF1000i.…”
Section: Discussionmentioning
confidence: 99%
“…However, high sensitivity could be shown with our parameter too, even with a cut-off of 10 4 cfu/mL [ 15 , 16 , 31 ]. Recently, a Swedish study presented a linear discriminant analysis using bacteria and leukocytes on a log scale [ 29 ] similar to Fig 2A . The parameters were slightly different from the parameters presented in this article, which might be due to another cut-off of urine culture bacterial growth (≥10 3 cfu/mL) and the use of Sysmex UF1000i.…”
Section: Discussionmentioning
confidence: 99%
“…Particle characterization is based on forward-scatter light, side-scatter light and fluorescence. Currently, flow cytometry has been used in clinical practice to detect culture-negative urine samples based on bacterial and WBC counts [10,11]. However, it has also been increasingly used as a screening method to rapidly identify positive urine samples with high bacterial concentration to perform direct identification and antimicrobial susceptibility testing [1214].…”
Section: Introductionmentioning
confidence: 99%
“…The underlying infecting bacteria on urine culture may influence urine dipstick results. In their report, Monsen et al found E coli present in 65% of cultures, followed by Enterococcus (8.2%), Klebsiella (7.2%), and Staphylococcus (5.0%); urine positive for E‐coli was associated with the highest urinary leucocyte count and all culture‐positive urine samples had leucocyte counts higher than that of controls, although these results did vary between the bacteria identified.…”
Section: Introductionmentioning
confidence: 91%